If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2lnx + ln(2x + -3) = ln(3x + -2) Reorder the terms: 2lnx + ln(-3 + 2x) = ln(3x + -2) 2lnx + (-3 * ln + 2x * ln) = ln(3x + -2) 2lnx + (-3ln + 2lnx) = ln(3x + -2) Reorder the terms: -3ln + 2lnx + 2lnx = ln(3x + -2) Combine like terms: 2lnx + 2lnx = 4lnx -3ln + 4lnx = ln(3x + -2) Reorder the terms: -3ln + 4lnx = ln(-2 + 3x) -3ln + 4lnx = (-2 * ln + 3x * ln) -3ln + 4lnx = (-2ln + 3lnx) Solving -3ln + 4lnx = -2ln + 3lnx Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '2ln' to each side of the equation. -3ln + 2ln + 4lnx = -2ln + 2ln + 3lnx Combine like terms: -3ln + 2ln = -1ln -1ln + 4lnx = -2ln + 2ln + 3lnx Combine like terms: -2ln + 2ln = 0 -1ln + 4lnx = 0 + 3lnx -1ln + 4lnx = 3lnx Add '-3lnx' to each side of the equation. -1ln + 4lnx + -3lnx = 3lnx + -3lnx Combine like terms: 4lnx + -3lnx = 1lnx -1ln + 1lnx = 3lnx + -3lnx Combine like terms: 3lnx + -3lnx = 0 -1ln + 1lnx = 0 Factor out the Greatest Common Factor (GCF), 'ln'. ln(-1 + x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-1 + x)' equal to zero and attempt to solve: Simplifying -1 + x = 0 Solving -1 + x = 0 Move all terms containing l to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + x = 0 + 1 x = 0 + 1 Combine like terms: 0 + 1 = 1 x = 1 Add '-1x' to each side of the equation. x + -1x = 1 + -1x Combine like terms: x + -1x = 0 0 = 1 + -1x Simplifying 0 = 1 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 0.63=logx | | 3(-5+h)-4(-5)= | | 3(25-2h+h^2)-4+4h-(4-3)= | | 9b^2+42bg+49g^2= | | 3(25-2h+h^2)-4+4h-(3-4)= | | 7(1-2h+h^2)-5+5h-(7-5)= | | 20n=60 | | y=192+1.04y | | 14+r=33 | | 5ab-8abc=0 | | 12+8+x+y=50 | | 4x+8x=109 | | X^3-4x^2-8x+12=0 | | 18+k=36 | | 5b=70 | | 0.5(0.2+x)=(0.32-2x)(0.2+x) | | m-7=7 | | 77+X+50+X+65=90 | | X+50+X+65=90 | | 3(4+2)=2(A-7) | | x^2-3x-10=2x+14 | | m+7=19 | | 15-4x=6+5x | | 16x^3-8x^2-24x=0 | | 0=y^2+4y-12 | | 3h-19h= | | (15x+18)=(23x-14) | | .25(5x-1)=8 | | 6(m-9)=18 | | -X^2+2X-3=-1 | | 1-logx=log(x+9) | | 625+3600=x^2 |